Model of Multi-energy Hub Cooperative Bargaining in Energy Internet - Xiping ZHU; Qian FU; Zilin LI; Jian LUO; Dengsong WANG (Zhongguo dianli)
The energy hub (EH) of energy internet is an effective way to realize the coordinated supply of multi energy and the complementary and optimized operation among energy regions. In order to realize the coordinated and economic operation of multiple energy hubs within a region and to ensure the interconnection of information flow and energy flow between different energy hubs, this paper constructs a multi energy hub coordination model based on the traditional energy hub model. At the same time, considering the cost of energy transaction between energy hubs, a cooperative bargaining model among multi energy hub operators is proposed. The simulation analysis shows that it can effectively reduce the operating cost of each operator, achieve the coordinated flow of energy flow between energy hubs, maximize the utilization of resources, and reduce the waste of energy.